Maqom dan Ahwal: Makna dan Hakikatnya dalam Pendakian menuju Tuhan - Asnawiyah Asnawiyah (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Religious teachings is important aspect for every person. The meaning of religious life for every adherent is to reach the highest degree before one‟s God. There  are many ways to to perfect human‟s spirit in order to reach the highest degree. In  Islam, human‟s degree is different from one to another before the Creator. The degree is  called maqam, which illustrates one position or degree. To reach the highest maqam,  one has to pass through many stages. In the order side, Islamic mysticism knows the  term of ahwal. Dissimilarly from maqam, ahwal is God‟s bestow to someone without need to great efforts. Since maqam is a position, which has to be reached by making  serious efforts, so the harder one sacrifices to pass through each maqam stage, the  nobler the one before the God.